Identification and functional characterization of a novel Acinetobacter pittii bacteriophage-encoded depolymerase - Zhang, Na; Li, Wei; Du, Xue; Daniyal, Danish; Feng, Meng-ai; Xu, Jiaoyang; Yang, Ziqin; Jiang, Hailin; Sheraz, Muhammad; Huang, Honglan; Banerjee, Santasree; Shi, Hongyan (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAcinetobacter pittii is increasingly recognized as a significant cause of nosocomial infections. Bacteriophage-encoded depolymerases that degrade capsular polysaccharides (CPS)—a major virulence factor of A. pittii—represent promising therapeutic tools.MethodsThis study identified and characterized a novel depolymerase, designated 31TSP, derived from the A. pittii bacteriophage 31Y. Its functional stability across various pH levels (5–11) and temperatures (4 °C to 121 °C) was assessed. The inhibitory effect of 31TSP on biofilm formation and its disruptive activity against preformed biofilms were evaluated using crystal violet staining, viable cell counts and scanning electron microscopy. Combinatorial treatments with 31TSP and ampicillin were conducted. Furthermore, the enzyme's stability under different ion concentrations (NaCl) and its ability to enhance serum bactericidal activity were tested under experimental conditions.ResultsCharacterization demonstrated that 31TSP exhibits a broad host range against A. pittii, A. baumannii, and A. nosocomialis. The enzyme degraded the CPS of host bacteria and displayed inhibition effects on sensitive hosts. 31TSP retained functional stability across a wide pH range (5–11) and temperatures from 4 °C to 121 °C. Its inhibitory effect on biofilm formation and disruptive activity against preformed biofilms were confirmed. Notably, combinatorial treatment with 31TSP and ampicillin significantly enhanced biofilm inhibition and disruption at 24 hours post-treatment. However, 31TSP did not maintain stability under different ion concentrations (NaCl) and could not enhance serum bactericidal activity under the experimental conditions.DiscussionThese findings support the potential of 31TSP as an antibacterial agent against Acinetobacter infections. The observed synergy with conventional antibiotics, such as ampicillin, suggests a promising combinatorial strategy for future therapeutics targeting Acinetobacter. The enzyme's stability under extreme conditions of temperature and pH further underscores its therapeutic potential. However, its instability in varying ionic environments and lack of serum bactericidal enhancement highlight aspects requiring further investigation for clinical application.